Challenges for shared responsibility – Political and social framing of coastal protection transformation in the Maldives - Ratter, Beate; Hennig, Arne; Zahid (DIE ERDE – Journal of the Geographical Society of Berlin, 2019)
There is widespread understanding that climate change has dramatic impacts especially for small islands. In the Maldives, a key challenge is to confront erosion processes along its coasts – past approaches have shown to not always be sustainable. Alternative approaches to coastal protection are therefore urgently needed. In this paper we use the concept of transformative governance to identify factors in society and politics that act as barriers and enablers to the introduction of alternative approaches to coastal protection in the Maldives. We investigate how inhabitants perceive coastal erosion risks and analyse people’s receptiveness to alternative coastal protection measures and their willingness to get involved in coastal protection. Governance structures are assessed against the context of conflicting central political, national and island peripherical interests. We identify hierarchical political structures in coastal protection governance as a dominant obstacle to alternative approaches. Based on empirical data collected in the research project DICES (Dealing with change in SIDS – societal action and political reaction in sea level change adaptation), we stress the importance of cultural aspects and sense of place when dealing with coastal protection. Further, we challenge the widespread assumption that people of the Maldives prefer hard coastal protection structures for their islands – a notion which is utilised by national politicians in their decision-making process to support the continuing application of hard protection measures. We discuss challenges to transformative governance related to shared responsibility, political power and openness to innovation.